Peningkatan Kemampuan Peternak dalam Pemanfaatan Ampas Tahu sebagai Pakan Ternak Kambing Melalui Proses Fermentasi Aspergillus niger dan Rhizopus oryzae di Desa Deli Tua Kecamatan Namorambe Kabupaten Deli Serdang - Yuan Alfinsyah Sihombing; Muhammad Zulham Efendi Sinaga; Rini Hardiyanti (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
The feed is the main ingredient in livestock breeding. The selection of good feed will increase livestock productivity. Many feeds can be made from waste such as tofu residue. Tofu residue is agro-industrial waste from tofu making process. The feed for goats/sheep provided by breeders in Deli Tua Village, Namorambe district, Deli Serdang regency, dominantly utilizes green grass. So it is necessary to make the alternative animal feed based on tofu residue by adding microorganisms such as Aspergillus niger and Rhizopus oryzae in the fermentation process. This community service applied the Participatory Action Research (PAR) method. The results show that the community members have succeeded in making fermented feed. The program not only increases the member’s skills but also livestock productivity both in terms of quality and quantity